GEOMORPHIC ANALYSIS OF THE CENTRAL RANGE FAULT, THE SECOND MAJOR ACTIVE STRUCTURE OF THE LONGITUDINAL VALLEY SUTURE, EASTERN TAIWAN - Shyu J.B.H.; Sieh K.; Chen Y.-G.; Chung L.-H. (My University, 2006)
Numerous landforms along the Longitudinal Valley suture of eastern Taiwan indicate that two opposing reverse faults currently dominate the suturing process between the Luzon volcanic arc and the Central Range of Taiwan. The east-dipping Longitudinal Valley fault, on the eastern flank of the valley, is well known. The west-dipping Central Range reverse fault, on the western flank of the valley, is more obscure. Nonetheless, it has produced many uplifted lateritic fluvial terraces along the eastern flank of the Central Range in the central reach of the valley, from just north of the Wuhe Tableland to near Chihshang. The fault appears to be active but blind south of Chihshang and inactive along the northern part of the Longitudinal Valley. The late Quaternary slip rate of the fault is less than 12.8 mm/yr. This constraint means that the fault is absorbing far less than half of the horizontal shortening across the Longitudinal Valley suture. However, the late Quaternary slip rate along the fault may be comparable to the uplift and exhumation rate of the Central Range. This suggests that localized brittle slip along the Central Range fault is an important component of crustal thickening and uplift of the range, even though additional shortening and crustal thickening may be occurring because of pervasive deformation beneath the range. © 2006 Geological Society of America.
Keywords: CENTRAL RANGE FAULT; EXHUMATION; LONGITUDINAL VALLEY; SUTURES; TAIWAN; TECTONIC GEOMORPHOLOGY; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная